Association between results of component-resolved diagnostics and basophil activation in Hymenoptera venom allergy: A registry-based cross-sectional study in adults - Krzysztof Łukasz Piwowarek; Krzysztof Kłos; Elżbieta Rutkowska; Andrzej Chciałowski; Agata Raniszewska-Borys; Iwona Kwiecień; Jerzy Kruszewski (PLoS ONE, 2026)
Background Allergy to Hymenoptera venom is one of the most frequent causes of anaphylaxis in adults. Conventional diagnostic approaches, including skin testing and measurement of allergen-specific IgE (sIgE) to venom extracts, do not always allow for precise identification of the culprit venom. This remains particularly challenging in patients with double-positive or inconclusive conventional test results, which may complicate the decision-making process regarding qualification for appropriate treatment. Component-resolved diagnostics (CRD) and the basophil activation test (BAT) may provide complementary information in such cases and aid in qualification for subcutaneous immunotherapy (SCIT). Methods In this retrospective registry-based cross-sectional study, 154 adults who had been evaluated for Hymenoptera venom allergy at the Military Institute of Medicine (Warsaw, Poland) between December 2023 and May 2025 were included. Patients were divided into three groups: not qualified for SCIT (n = 27), qualified for bee venom immunotherapy (n = 32), and qualified for wasp venom immunotherapy (n = 95). Serum sIgE to venom extracts and certain components (rApi m 1, m 2, m 3, m 5, m 10; rVes v 1, v 5) were measured. BAT was performed by flow cytometry assessing CD63 expression. Results Moderate correlations were found between BAT results and sIgE to rApi m 1 (rho = 0.495; p < 0.001) and rVes v 5 (rho = 0.456; p < 0.001). No correlation was observed for rVes v 1, and negative correlations were noted between rApi m 1 and rVes v 5 in heterologous BAT responses. No statistically significant association was observed between the severity of previous sting reactions and BAT or sIgE parameters. However, due to limited subgroup sizes, these analyses were underpowered and the results should be interpreted as inconclusive. Conclusions Among the examined variables, the major components Api m 1 and Ves v 5 were the most strongly correlated with specific basophil activation in vitro. The combined use of CRD and BAT may support clinical assessment and facilitate decisions regarding immunotherapy qualification. Further prospective studies are warranted to assess the prognostic and clinical relevance of our findings.